Antenatal characteristics of Roma female population in Virovitica-Podravina County, Croatia - Šegregur Jadranko; Šegregur Domagoj (Sciendo, 2017)
This study reports about antenatal characteristics of Roma minority population. The study was designed to investigate data about health behaviours known to be associated with reproductive outcomes of Roma women that have very good living conditions and relatively high resource availability.